Evaluation of the pore morphologies for piezoelectric energy harvesting application. Issue 4 (15th February 2022) - Yan, Mingyang; Liu, Shengwen; Xiao, Zhida; Yuan, Xi; Zhai, Di; Zhou, Kechao; Zhang, Dou; Zhang, Guodong; Bowen, Chris; Zhang, Yan
Abstract: Piezoelectric energy harvesting has attracted significant attention in recent years due to their high-power density and potential applications for self-powered sensor networks. In comparison to dense piezoelectric ceramics, porous piezoelectric ceramics exhibit superiority due to an enhancement of piezoelectric energy harvesting figure of merit. This paper provides a detailed examination of the effect of pore morphology on the piezoelectric energy harvesting performance of porous barium calcium zirconate titanate 0.5Ba(Zr0.2 Ti0.8 )O3 -0.5(Ba0.7 Ca0.3 )TiO3 (BCZT) ceramics. Three different pore morphologies of spherical, elliptical, and aligned lamellar pores were created via the burnt-out polymer spheres method and freeze casting. The relative permittivity decreased with increasing porosity volume fraction for all porous BCZT ceramics. Both experimental and simulation results demonstrate that porous BCZT ceramics with aligned lamellar pores exhibit a higher remanent polarization. The longitudinal d 33 piezoelectric charge coefficient decreased with increasing porosity volume fraction for the porous ceramics with three different pore morphologies; however, the rate of decrease in d 33 with porosity is slower for aligned lamellar pores, leading to the highest piezoelectric energy harvesting figure of merit. Moreover, the peak power density of porous BCZT ceramics with aligned lamellar pores is shown to reach up to 38 μW cm -2 when used as an energy harvester, which is significantly higher than that of porous BCZT ceramics with spherical or elliptical pores. This work is beneficial for the design and manufacture of porous ferroelectric materials in devices for piezoelectric energy harvesting applications.